Bicycle traffic in the Czech Republic: The ways of influencing the behaviour of people involved in it. - Sucha, Matús (Palacký University, 2017)
The main objectives of the present paper are to provide general information about the development and safety of bicycle traffic in the Czech Republic and the ways of influencing the behaviour of road users to promote a higher share of bicycle traffic and increase the safety of cyclists. A theoretical model of influences on road users' behaviour, applied to the issue of bicycle traffic, was used for this purpose. The safety of cyclists in the Czech Republic still seems to be rather low in comparison with other developed countries of the EU (such as the Netherlands, Denmark, and Germany), where, moreover, the intensity of cycle traffic is much higher than in the Czech Republic. According to the police figures, evidence indicates that a cyclist in the Czech Republic is at a 4.5 times higher risk of being killed in a traffic accident than a cyclist in the Netherlands. An urban area must offer mobility for everybody to be a pleasant place to live. Progress in transportation means improving conditions for all modes of transport. It is not the faster, motorised modes of transport that should get priority; the emphasis should be placed on sustainability, safety, and comfort. In the Czech Republic the major barriers which prevent higher rates of cyclists in urban areas and compromise their safety include: the insufficient quality of the surfaces of cycling paths (or their absence), cycling paths not being interconnected into a coherent network, a lack of places where bicycles can be parked securely, and a lack of facilities at workplaces for people who use bicycles to get to work. However, one of the main obstacles to a higher rate of bicycles being used as means of transport is generally the cyclists' low subjective feeling of safety, especially with regard to roads used together with cars.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrssicherheit; Radfahrer; Verhalten; Verkehrsverhalten; Smart City